Metformin attenuates depressive-like behaviour of methamphetamine withdrawal in mice: A mechanistic approach - Hosseini, Mir-Jamal; Arabiyan, Aisan; Mobassem, Sina; Ghavimi, Hamed (Taylor & Francis Ltd, 2023)
Objectives Methamphetamine (METH) as a potent psychostimulant drug with a high potency of dependence rate that results in neurotoxicity has become a major drug of abuse in many parts of the world. Unfortunately, there is limited evidence regarding treatment of METH withdrawal syndrome. Therefore, we aimed to investigate whether metformin mitigate the methamphetamine (METH) withdrawal syndrome in male mice. Based on the literature, depression and anxiety are the major METH withdrawal symptoms. Methods Here, METH (2 mg/kg) was administered to mice twice a day for 14 constitutive days to induce animal model of METH-induced withdrawal syndrome. To do this, mice in control group and those with METH withdrawal syndrome were divided into treatment (receiving metformin in 3 doses of 50, 100 and 200 mg/kg for 10 days) and non-treatment sub-groups. Following the behavioural test, the animals were sacrificed; their hippocampus was dissected to measure oxidative stress parameters and expression of cellular energy homeostasis and immune-inflammatory genes. Results Our data revealed that metformin provoked antidepressant effects in behavioural tests through AMPK overexpression as an important mitochondrial energetic sensor and inhibition of Tlr4 overexpression in the immune system gene expression. In addition, metformin was able to improve oxidative stress biomarkers and neuronal damage in the hippocampus and restore cellular energy homeostasis and immune system gene expression. Conclusions The data suggested that metformin can influence the hippocampus through targeting mitochondria and their performance, and consequently, neuroinflammation responses and brain metabolic changes. It is supposed to be a new therapeutic option in clinical trials of depression and anxiety following METH withdrawal treatment.
Keywords: Methamphetamine (METH); Metformin; Depression; Anxiety; Tlr4; AMPK; Oxidative stress; Withdrawal syndrome; Mice